Predictors of Acute Kidney Injury in Hospitalized Dengue Patients: A Cross-sectional Study - Rahman, Shaila; Wazib, Amit; Ahmed, Rayhan; Bahar, Tamanna (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Dengue is an endemic RNA viral infection in Bangladesh. It can affect different organ systems, acute kidney injury (AKI) is one of them. The study aimed to detect the prevalence and predictors of dengue-associated acute kidney injury (DAKI) and in-hospital outcome. Methods: This cross-sectional study was carried out from July to September 2023 at the peak of dengue outbreak in the Department of Medicine in Shaheed Monsur Ali Medical College Hospital, Dhaka, Bangladesh. A total of 203 confirmed cases of dengue aged > 12 years were finally included in the study. Results: The prevalence of DAKI was 7.9%. The mean age of DAKI cases was higher than the non-AKI cases (p-value 0.008). AKI was significantly associated with DHF (43.8% vs 17.6%), higher HCT, higher neutrophil count and lower lymphocytes. In multivariate analyses age more than 60 years, dengue haemorrhagic fever (DHF) and multiple organ dysfunction (MODS) were the independent predictors of DAKI. AKI itself was the independent predictor of hospital stay for more than three days (OR 4.67; 95% CI 1.29-16.92). There was no mortality in the study participants. All were discharged home with resolved AKI. Conclusion: Age more than 60 years, DHF and MODS are the independent risk factors of DAKI. Future studies are required to find out the risk factors for early diagnosis and prompt management. J Bangladesh Coll Phys Surg 2023; 41: 29-33